DO RISK, BUSINESS CYCLE, AND COMPETITION AFFECT CAPITAL BUFFER? AN EMPIRICAL STUDY ON ISLAMIC BANKING IN ASEAN AND MENA - Maharani, Novita Kusuma; Setiyono, Bowo (Bank Indonesia, 2018)
Basel III guidelines were released in 2010 by the Basel Committee on Banking Supervision (BCBS) as a revision of the previous Basel guidelines with the aim of strengthening the bank's capital and liquidity of banks. BCBS formulate a new policy that is the capital buffer. Capital Buffer is the difference between the minimum capital required by regulators with its overall capital and is considered a